Genetic analysis of cold tolerance at seedling stage and heat tolerance at anthesis in rice (Oryza sativa L.) - Cheng, Lirui; Wang, Junmin; Uzokwe, Veronica; Meng, Lijun; WANG, Yun; Sun, Yong; Zhu, Ling-Hua; Xu, Jianlong; Li, Zhikang (Elsevier, 2012)
A set of 240 introgression lines derived from the advanced backcross population of a cross between a japonica cultivar, Xiushui 09, and an indica breeding line, IR2061, was developed to dissect QTLs affecting cold tolerance (CT) at seedling stage and heat tolerance (HT) at anthesis. Survival rate of seedlings (SRS) and spikelet fertility (SF), the index traits of CT and HT, showed significant differences between the two parents under stresses. A total of four QTLs (qSRS1, qSRS7, qSRS11a and qSRS11b) for CT were identified on chromosomes 1, 7, 11, and the Xiushui 09 alleles increased SRS at all loci except qSRS7. Four QTLs for SF were identified on chromosomes 4, 5, 6, and 11. These QTLs could be classified into two major types based on their behaviors under normal and stress conditions. The first was QTL expressed only under normal condition; and the second QTL was apparently stress induced and only expressed under stress. Among them, two QTLs (qSF4 and qSF6) which reduced the trait difference between heat stress and normal conditions must have contributed to HT because of their obvious contribution to trait stability, and the IR2061 allele at the qSF6 and the Xiushui 09 allele at the qSF4 improved HT, respectively. No similar QTL was found between CT at seedling stage and HT at anthesis. Therefore, it is possible to breed a new variety with CT and HT by pyramiding the favorable CT- and HT-improved alleles at above loci from Xiushui 09 and IR2061, respectively, through marker-assisted selection (MAS).